Evaluation of Life Skills Based Education Programs in Madrasa - Siswadi Siswadi (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2020)
This research is intended to describe the evaluation of life skills-based educational programs in MTs and MA Modern al-Azhary. This study uses a qualitative approach to the type of case study research. Through program evaluation, the results of the study indicate that there are four problems in education programs based on life skills. First, the problem of preparing education plans based on life skills. Second, problems in organizing education based on life skills. Third, problems in implementing life skills-based education. Fourth, problems in the supervision of education based on life skills. These four problems are caused by various factors, namely: the factor of human resources which is minimal in managerial ability, the factor of limited facilities and infrastructure, as well as the factors that have not been made to improve the education program sustainably based on life skills both by the management and the teachers and administrators of the foundation. Based on the problem and the cause of the problem then efforts are made to improve, including strengthening the managerial competence of the madrasah head and his deputy, strengthening the pedagogical and professional competence of teachers, procuring facilities and infrastructure based on the priority scale, as well as following up on supervision results. Life skills-based education programs in MTs and MA Modern al-Azhary have experienced success, that is, each target that has been determined in various activities in the life skills-based education program can be achieved.